Bacteria from gut microbiota associated with diarrheal infections in children promote virulence of Shiga toxin-producing and enteroaggregative Escherichia coli pathotypes - Izquierdo, Mariana; Lopez, Joaquín; Gallardo, Pablo; Vidal, Roberto M.; Ossa, Juan C.; Farfan, Mauricio J. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Diarrheagenic E. coli (DEC) pathogenicity relies on the interaction of bacteria with the host’s gut environment, which is regulated by the resident microbiota. Previously, we identified indicative bacterial species of gut microbiota in DEC-positive stool samples from children. Here, we evaluated the role of two indicative species, Citrobacter werkmanii (CW) and Escherichia albertii (EA), in the virulence of two DEC pathotypes, Shiga toxin-producing (STEC) and enteroaggregative (EAEC) Escherichia coli. Methods We determined the effect of supernatants obtained from CW and EA cultures on the gene expression of STEC strain 86-24 and EAEC strain 042 by RNA-seq analysis. We evaluated IL-8 secretion from T84 cells infected with these DEC strains in the presence or absence of the supernatant from EA. The effect of the supernatant from EA on the growth and adherence of STEC and EAEC to cells was also evaluated. Finally, we studied the effect of the EA supernatant on the STEC-induced inflammation mediated by the long polar fimbriae (Lpf) in T84 cells and the expression of plasmid-encoded toxin (Pet) in EAEC. Results RNA-seq analysis revealed that several virulence factors in STEC and EAEC were upregulated in the presence of supernatants from CW and EA. Interestingly, an increase in the secretion of IL-8 was observed in cells infected with STEC or EAEC in the presence of a supernatant from EA. Similar results were observed with the supernatants obtained from clinical strains of E. albertii. The supernatant from EA had no effect on the growth of STEC and EAEC, or on the ability of these DEC strains to adhere to cells. We found that Pet toxin in EAEC was upregulated in the presence of a supernatant from EA. In STEC, using mutant strains for Lpf fimbriae, our data suggested that these fimbriae might be participating in the increase in IL-8 induced by STEC in cells in the presence of a supernatant from EA. Conclusion Supernatant obtained from an indicative species of DEC-positive diarrhea could modulate gene expression in STEC and EAEC, and IL-8 secretion induced by these bacteria. These data provide new insights into the effect of gut microbiota species in the pathogenicity of STEC and EAEC.